2018
DOI: 10.1080/01639625.2018.1461786
|View full text |Cite
|
Sign up to set email alerts
|

Under the Corporate Radar: Examining Insider Business Cybercrime Victimization through an Application of Routine Activities Theory

Abstract: Cybercrime is recognized as one of the top threats to UK economic security. On a daily basis, the computer networks of businesses suffer security breaches. A less explored dimension of this problem is cybercrimes committed by insiders. This paper provides a criminological analysis of corporate insider victimization. It begins by presenting reviews of insider criminal threats and routine activities theory as applied to cybercrime. Analysis of the nationally representative Cardiff University UK Business Cybercri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 26 publications
2
47
1
Order By: Relevance
“…We have applied the theoretical framework of RAT and the elements of VIVA to analyze the impact of businesses' online activities and cybersecurity measures, as indicators of various forms of capable guardianship and suitability of crime targets, on cybercrime victimization, as suggested in previous research (e.g., Miró Llinares and Johnson, 2017;Newman and Clarke, 2003;Williams et al, 2019;Yar, 2005). We have combined the use of modeling approaches traditionally used to study cybercrime victimization (i.e., logistic regression models for binary victimization outcomes, see Bossler et al, 2012;Leukfeldt and Yar, 2016;Williams et al, 2019) with novel approaches to analyze the negative impact and harms of cybercrime victimization on organizations (e.g., Paoli et al, 2018) and the number of crimes suffered by businesses and charities. This gives us information not only about the likelihood of organizations reporting falling victim to at least one cybersecurity breach, but also the likelihood of suffering the negative consequences of such criminal activities, and the number of crimes they may face.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have applied the theoretical framework of RAT and the elements of VIVA to analyze the impact of businesses' online activities and cybersecurity measures, as indicators of various forms of capable guardianship and suitability of crime targets, on cybercrime victimization, as suggested in previous research (e.g., Miró Llinares and Johnson, 2017;Newman and Clarke, 2003;Williams et al, 2019;Yar, 2005). We have combined the use of modeling approaches traditionally used to study cybercrime victimization (i.e., logistic regression models for binary victimization outcomes, see Bossler et al, 2012;Leukfeldt and Yar, 2016;Williams et al, 2019) with novel approaches to analyze the negative impact and harms of cybercrime victimization on organizations (e.g., Paoli et al, 2018) and the number of crimes suffered by businesses and charities. This gives us information not only about the likelihood of organizations reporting falling victim to at least one cybersecurity breach, but also the likelihood of suffering the negative consequences of such criminal activities, and the number of crimes they may face.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of private organizations this is even more likely to be the case, given that details of organizations' revenues are often publicly available. Others argue, however, that in cyberspace the 'value' is frequently an expression of information as a route to financial gain (Wall, 2007;Yar, 2005), and Williams et al (2019) found that organizations with confidential customer information were more likely to suffer insider business cybercrime victimization. Our model results show that those organizations that store personal information suffer more cyber-attacks, although this variable does not predict the negative impacts of cybercrime (e.g., loss of access to files, systems corrupted, stopped staff from carrying out their daily work).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question as to whether cybercrime is a component of white collar crime; or conversely, whether the increasing use of computers in the workplace means that we should rethink this taxonomy, perhaps even classifying white collar crime as a class of cybercrime. The increasing prevalence of digital technology means more offending in the workplace is likely to involve computers [6], [7]. Workplace offenders may not necessarily be of high social status, but the availability of new technologies provides many opportunities for innovation at work, both criminal and legitimate.…”
Section: A Cybercrime In the Workplace-a Form Of White Collar Crime?mentioning
confidence: 99%
“…The detection rate in the United States is even lower based on estimates of the magnitude of white-collar crime by the National White-Collar Crime Center (Huff et al, 2010) and the Association of Certified Fraud Examiners (ACFE, 2008, 2014, 2016). Offenders tend to move under the radar (Williams, 2019).…”
Section: Introductionmentioning
confidence: 99%